2006
DOI: 10.1038/ncb1476
|View full text |Cite
|
Sign up to set email alerts
|

Oocyte signals derived from polyunsaturated fatty acids control sperm recruitment in vivo

Abstract: A fundamental question in animal development is how motile cells find their correct target destinations. During mating in the nematode Caenorhabditis elegans, males inject sperm through the hermaphrodite vulva into the uterus. Amoeboid sperm crawl around fertilized eggs to the spermatheca--a convoluted tube where fertilization occurs. Here, we show that polyunsaturated fatty acids (PUFAs), the precursors of eicosanoid signalling molecules, function in oocytes to control directional sperm motility within the ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
253
1
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(265 citation statements)
references
References 28 publications
8
253
1
3
Order By: Relevance
“…Vit-1, 2, 3, 4, 5, and 6 were also present (Table I). Vit proteins are apolipoprotein homologs believed to transport lipids to growing oocytes during yolk deposition (33). Western blotting analysis showed that Vit-2 was only partially associated with LDs and the main signal was in total membrane fraction (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Vit-1, 2, 3, 4, 5, and 6 were also present (Table I). Vit proteins are apolipoprotein homologs believed to transport lipids to growing oocytes during yolk deposition (33). Western blotting analysis showed that Vit-2 was only partially associated with LDs and the main signal was in total membrane fraction (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…C18 and C20 polyunsaturated fatty acids (PUFAs) have been shown to effect directed sperm movement towards the spermatheca and the formation of synaptic vesicles in neuronal tissues. [18,19] FAT-3 mutants lack the delta6 fatty acid desaturase and so cannot convert linoleic acid into C20 PUFAs because this desaturase activity is a prerequisite to subsequent elongase activity. [20] These mutants show a number of defects which are rescued by dietary supplementation of C20 and C18 PUFAs, including smaller brood size, alterations in the defecation cycle, and defects in chemotaxis.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, when genes involved in the synthesis are mutated, spermatozoa become partly defective in their relocation from the uterus into the spermatheca. [18][19][20] These phenotypes seem similar to those of spe-9 and spe-45 mutants, resulting in the incomplete sperm recruitment into the spermatheca. Currently the sperm prostaglandin-receptor(s) is not known, but SPE-9 and/or SPE-45 could function in the prostaglandin binding to spermatozoa and/or subsequent sperm reaction(s).…”
Section: Introductionmentioning
confidence: 51%